Mechanical properties and durability against the dry termite attacks of particleboard made from bamboo with citric acid as adhesive - Ragil Widyorini; Ari Puspa Yudha; Ganis Lukmandaru; Tibertius Agus Prayitno (Jurnal Ilmu Kehutanan)
Research on development of citric acid as natural adhesive are still limited. Therefore this research focused on effects of citric acid content and pressing temperature on properties of particleboard made from bamboo, including its durability to the dry termite attacks. Petung bamboo particles were used as raw materials. Chemical characteristics of petung bamboo were analyzed for its extractive, lignin, holocellulose and alpha cellulose. Factors used in this research were citric acid content (0 - 40 %) based on dry weight particles and pressing temperature (200 oC dan 220 oC). Properties of the particleboard were analyzed based on Japanese Industrial Standard (JIS) A 5908 for particleboard. Fourier transform infrared spectroscopy (FTIR) analysis was used for investigating the changes of ester groups at various citric acid content and pressing temperature. The dry termite resistance was then analyzed for its weight loss and mortality after 6 weeks. The results showed that interaction between two factors affected significantly on thickness swelling, water absorption, modulus of elasticity, and modulus of rupture. Intensity of C=O groups became stronger as increasing citric acid content, providing high mechanical properties and high dimensional stability. Optimum condition in this research was achieved at 20 % of citric acid content and 200 oC of pressing temperature, which the board properties met the requirement of JIS A 5908 type 8. Increasing of citric acid content would also increase the dry termite mortality. Addition of 20 % citric acid at 200 oC of pressing temperature produced particleboard with the weight loss was 0.9 % and 57 % of the dry termite mortality.